Torque characteristics of guide vanes protection device of Francis turbine in hydropower plant. (September 2021) - Xu, Jiawen; Lei, Dong; He, Jintao; Zhou, Kaiyang; Xu, Yongmin; Bai, Pengxiang; Zhu, Feipeng
Highlights: The performance of protection devices for a hydro-power plant is analyzed. The operation mechanism and torque distribution mode of shear pin and friction device is investigated. Three different loading tests were carried out. The curves of torque change under different loading conditions are provided. Abstract: Water turbines are widely used in water conservancy project and failure of it will have a great impact on the project safety and social benefits. Consequently, it is necessary to take protective measures and equip protective devices for turbines. This study investigates the torque characteristics of guide vane protection devices in a hydropower plant through controlled variable experiment. The investigation includes the operation mechanism and torque distribution mode of the guide vane protection devices working independently and collaboratively. The results show that the torque distribution ratio of the friction device continuously reduces with the increase of load, on the contrary, the distribution ratio of the shear pin increases. With the increase of load, the torque borne by the friction device and shear pin increases continuously, when the friction device reaches the limit state, friction failure occurs. Therefore, in the combination condition, the load can be set at the torque distribution intersection point as far as possible to effectively extend the working time of the protection device in case of accidents. Moreover, it can also extend the overall life of the protection devices.